Analysis of the Relationship Between Work Engagement, Job Satisfaction, and Human Resource Performance at Bluduptd Salotungo Public Health Center, Soppeng Regency - Ulfa Namirah; Julia Fitrianingsih; Hairuddin K.; Bachtiar Baso; Indar Indar (Majapahit Journal of Islamic Finance and Management, 2026)
Human resources (HR) constitute a key determinant in the delivery of healthcare services at public health centers. Challenges such as high workloads, limited staffing, and low levels of motivation may adversely affect job satisfaction and HR performance. One psychological factor that plays a crucial role is work engagement, defined as an individual’s positive, fulfilling involvement in their work. This study aims to analyze the relationship between work engagement, job satisfaction, and HR performance at BLUD UPTD Salotungo Public Health Center, Soppeng Regency. The study employed a quantitative analytic design with a cross-sectional approach. The population and sample comprised all health and non-health personnel, totaling 101 employees, selected using a total sampling technique. Data were collected using the Utrecht Work Engagement Scale (UWES), the Job Satisfaction Survey (JSS), and performance assessments based on Key Performance Indicators (KPIs). The data were analyzed using Pearson correlation and multiple linear regression tests. The results indicate that work engagement has a positive and significant relationship with both job satisfaction and HR performance. Job satisfaction also shows a stronger positive association with HR performance and functions as a mediating variable in the relationship between work engagement and performance. The findings confirm that simultaneous improvements in work engagement and job satisfaction contribute to enhanced HR performance. Accordingly, public health center management should develop human resource policies oriented toward improving employees’ psychological well-being and job satisfaction in order to support sustainable healthcare service quality.